The management of abandoned project by local authority in Selangor / Mohd Sharafuddin Azaly Mohd Shukry - Mohd Shukry, Mohd Sharafuddin Azaly (Faculty of Architecture, Planning and Surveying, 2015)
Abandoned of housing projects amid construction is a primary issue that the housing sector in Malaysia has been encountering since 1980s. Elements relating to projects be abandonment can be categorize into many factors such as financial management, economic, mismanagement, developer, social and etc for the causes in different LA. From the factors that contribute to abandoned project, the impact of the causes also will get such as in term of economic and social. This research aims to analyze management on abandoned projects by different local authority (LA) in Selangor, Malaysia with several objective which are first is to identify the causes and impact of abandoned projects in different LA, second is to identify the problems faced by different LA in managing the abandoned projects and lastly is to identify the methods use by different LA on managing the abandoned projects in Selangor, Malaysia. Ten of different LA in Selangor, Malaysia is involved in this research for data collection through structured interview at each of the LA. This research also will clearly explain about what are problems faced and the methods used by different LA on managing the abandoned project. In view of the fact that, people are many different opinions may arise from time to time. All the problems mentioned has the solutions on how to deal with it. As the researcher they are several methods to reduce the problem that occurrences to accomplish the aim of this research which to reduce the abandoned project in construction industry. In a nutshell, hopefully in the future, the contractor in our industry can be more effective toward the completing the project in date line.